Advances in organoid technology for veterinary disease modeling - Chen, Bo; Slocombe, Ronald Francis; Georgy, Smitha Rose (Frontiers in Veterinary Science, 2023)
Organoids are in vitro organ-like structures that faithfully recapitulate many characteristics of a specific organ. During the past decades, major progress has been accomplished in establishing threedimensional (3D) culture systems toward stem cell-derived organoids. As a significant technological breakthrough, these amazing 3D organoid constructs bridge the conventional 2D in vitro models and in vivo animal models and provide an unprecedented opportunity to investigate the complexities of veterinary diseases ranging from their pathogenesis to the prevention, therapy, or even future organ replacement strategies. In this review, we briefly discuss several definitions used in organoid research and highlight the currently known achievements in modeling veterinary diseases, including infectious and inflammatory diseases, cancers, and metabolic diseases. The applications of organoid technology in veterinary disease modeling are still in their infancy stage but the future is promising.